Implementing streambank erosion control measures in meandering streams: design procedure enhanced with numerical modelling. Issue 3 (3rd July 2017) - Elhakeem, Mohamed; Papanicolaou, A.N. (Thanos); Wilson, Christopher G.
ABSTRACT: Dike structures have been used in many streams to control streambank erosion by redirecting the flow away from the banks towards the centre of the channel. In this study, the 2D finite-element surface water modelling system (FESWMS) was used to enhance the design of dike structures in two meandering stream reaches along the Raccoon River, Iowa, USA. FESWMS was used to find the optimal number and spacing between the dikes and to access their overall performance in controlling river-bank erosion in the study reaches. The study included also field measurements for model calibration and verification. The model results showed that the proposed dike structures, consisting of alternate five bendway weirs and four spurs at each site with a spacing of about 50 m, successfully reduced the flow velocity along the outside bank and increased the conveyance of the flow to the stream centre. The average lengths of the spurs and bendway weirs were about 16 and 32 m, respectively. The estimated velocity and Froude number values along the outside riverbank where the dikes were constructed were less than 1.0 m/s and 0.3, respectively, which are within the recommended values for erodible channel stability design. Site visits one year after the dike construction showed that the dikes were successful in controlling streambank erosion by allowing incoming sediment to deposit between the dikes and along the bank line. Sediment transport measurements at the study sites showed that the maximum deposition was about 0.8 m, which is much higher than a typical averaged deposition value of about 0.3 m/year. Further, recent Google Earth pictures for the sites showed that the bank slope lines almost recovered back in their original profiles and that the dikes became part of the restored banks, a strong indication of the success of the proposed dikes design.